Brain Volume and Perception of Cognitive Impairment in People With Multiple Sclerosis and Their Caregivers - Fenu, Giuseppe; Lorefice, Lorena; Carta, Elisa; Arru, Mauro; Carta, Alice; Fronza, Marzia; Coghe, Giancarlo; Frau, Jessica; Contu, Franco; Barracciu, Maria Antonietta; Cocco, Eleonora (Frontiers in Neurology, 2021)
Background: Cognitive impairment (CI) is common in people with multiple sclerosis (pwMS). The assessment of CI is based on neuropsychological tests and accurate anamnesis, involving the patients and caregivers (CG). This study aimed to assess the complex interplay between self-perception of CI, objective CI and the brain atrophy of MS patients, also exploring the possible differences with CI evaluated by caregivers. Methods: Relapsing pwMS were enrolled in this study. Subjects underwent neuropsychological examination using the Brief Cognitive Assessment for Multiple Sclerosis (BICAMS) and evaluation of self-reported cognitive status using the patient-version of the Multiple Sclerosis Neuropsychological Questionnaire (p-MSNQ). Depression and anxiety were also evaluated using the Back Depression Inventory-version II (BDI-II) and Zung Anxiety Scale. Brain MRI images were acquired and brain volumes estimated. For each patient that was enrolled, we spoke to a caregiver and collected their perception of the patient's CI using the MSNQ- Caregiver version. Results: Ninety-five MS subjects with their caregivers were enrolled. CI was detected in 51 (53.7%) patients. We found a significant correlation (p < 0.001) between BICAMS T scores and lower whole brain (Rho = 0.51), gray matter (Rho = 0.54), cortical gray matter (Rho = 0.51) volumes and lower p-MSNQ (Rho = 0.31), and cg-MSNQ (Rho = 0.41) scores. Multivariate logistic regression showed that p-MSNQ is related to a patient's anxiety to evaluate by Zung Score (p < 0.001) while cg-MSNQ to patient's brain volume (p = 0.01). Conclusion: Our data confirm that neuropsychological evaluation results are related to the perception of CI and brain volume measures and highlight the importance of the caregiver's perception for cognitive assessment of pwMS.